2021
DOI: 10.1016/j.abrep.2021.100388
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on substance use among adults without children, parents, and adolescents

Abstract: Highlights Alcohol and substance use problems increase after the COVID-19 pandemic onset. Research methods included surveys and analysis of pre-to-post change. Particulary great increases in alcohol and substance use were found in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 19 publications
4
27
0
Order By: Relevance
“…For example, a 17% and 24% decline in marijuana and alcohol availability in the USA was reported during the pandemic; given the situation of substance unavailability in the USA, the substance use rates had not significantly decreased [ 36 ]. Despite these findings, other studies reported increased substance use among adolescents during the pandemic of 25.33% and 9.33% increment in alcohol and other substance use, respectively [ 37 ].…”
Section: Discussionmentioning
confidence: 94%
“…For example, a 17% and 24% decline in marijuana and alcohol availability in the USA was reported during the pandemic; given the situation of substance unavailability in the USA, the substance use rates had not significantly decreased [ 36 ]. Despite these findings, other studies reported increased substance use among adolescents during the pandemic of 25.33% and 9.33% increment in alcohol and other substance use, respectively [ 37 ].…”
Section: Discussionmentioning
confidence: 94%
“…The UNODC’s 2021 World Drug Report states an increase in drug abuse due to the socio-economic impact of the COVID-19 pandemic and associated stress and anxiety [26] . Authors from other studies have also cautioned about an increase in deviant behaviour due to the psychological impact of coronavirus on life and livelihood [27] , [28] . Further research is warranted to look into behavioural patterns of voluntary and replacement blood donors and correlate with the prevalence of transfusion-transmitted infections.…”
Section: Discussionmentioning
confidence: 99%
“…Research looking at the relationship between grief and mental health of college students during the COVID‐19 pandemic showed that individuals who lost loved ones as a result of COVID‐19 had increased psychological distress. The most common mental health problems experienced by young adults during the pandemic were anxiety, depression, and alcohol and substance use (Dodge et al, 2021 ; Li et al, 2021 ). In addition, previous research has demonstrated a negative relationship between mental health and psychological hardiness (Sadeghi & Einaky, 2021 ).…”
Section: Discussionmentioning
confidence: 99%